Abnormalities of horizontal gaze. Clinical, oculographic and magnetic resonance imaging findings. I. Abducens palsy. Issue 3 (March 1990) - Bronstein, A M; Morris, J; Du Boulay, G; Gresty, M A; Rudge, P
Abstract : Fifty one patients with abnormalities of horizontal gaze were studied with magnetic imaging of the brain (MRI) and eye movement recordings to identify the loci of lesions responsible for isolated abducens palsy, conjugate gaze palsy and different types of internuclear ophthalmoplegias. The lesions responsible for a particular disorder were identified by overlapping enlarged drawings of the individual scans at comparable brain-stem levels and identifying the areas where the abnormal MRI signals intersected. A statistical procedure was devised to exclude the possibility that the areas of overlap occurred by chance. In this paper, the findings in the group of patients with VI nerve palsy are reported since the location of their lesions could be predicted from known anatomy, so validating the procedure. The results were independently obtained with the overlapping technique and the statistical procedure and showed that the lesions were located in a region corresponding to the posterior part of the abducens fasciculus. This confirms that central lesions producing isolated lateral rectus weakness spare the abducens nuclei. The agreement between the procedures used and earlier clinical and experimental results suggest that the method we describe can be applied to locate the site of lesions on MRI scans in other groups of patients with more complex gaze disorders.